Analysis of Parental Assessment of the Usefulness of Expert Systems in Detecting Child Behavioral Disorders - Nurhayati Nurhayati; Eni Nur Rahmawati; Imanuel Dwi Anand Sinar Putra; Dimas Rizky Maulana (International Journal of Health and Medicine, 2025)
This study discusses the analysis of parental assessment and the usefulness of expert systems in detecting child behavioral disorders using the system usability method scales (SUS). This system is designed to help parents identify behavioral disorders in children efficiently and accurately. The research method includes compiling a questionnaire, collecting data, processing SUS scores, interpreting results, and recommending improvements. The results of this study indicate that this system gets an average SUS score of 82.84, which is included in the Grade A category. This shows a high level of acceptance and good user experience, where users do not experience difficulty in operating the system. In addition, this system managed to maintain its search performance, but improvements are needed in some of its services according to suggestions from respondents.